Relevansi Pembiayaan Pemilikan Rumah (PPR) Syariah dalam Penyelesaian Pembiayaan Bermasalah Bernilai Humanis Islami - Kurnaemi Anita; Muhammad Wahyuddin Abdullah; Muhammad Nirwan Idris (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Preference in solution construction of non-performing financing based on Islamic business ethics was born from the accumulation of fiqh of muamalah conceptions. This study aimed to describe the PPR mechanism according to sharia standards and to identify the relevance of sharia PPR practices in producing non-performing financing with Islamic humanist values based on fiqh of muamalah. This is qualitative research with a phenomenological approach to the Sharia Property Developer PT. Wahana Persada Indonesia. Data collection was conducted through observation and interviews with the president director, accounts receivable staff, marketing staff, and several users. This research describes the flow of financing that occurs in the field, starting from the location survey to the implementation of the Sale and Purchase Agreement and the handover of homeownership certificates. Besides, this study also finds three types of handling of problematic financing qualifications applied by developers in each cluster, starting from soft connections, restructuring, and finding a replacement for users. This is then made relevant to the values of Islamic business ethics to create an Islamic humanist financing atmosphere.